2017
DOI: 10.2135/cropsci2016.12.1008
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Single Mepiquat Chloride Application at Different Growth Stages with Climate, Cultivar, and Plant Population for Cotton Yield

Abstract: Cotton (Gossypium hirsutum L.) yield responses to the plant growth regulator mepiquat chloride (1,1‐dimethyl piperidinium chloride, MC) are associated with climate, cultivar, and plant population. However, the interactions of these factors with MC for yield are inconsistent or unexpected. We hypothesize that climate (mainly precipitation), cultivar, and plant density only interact with MC applied at specific growth stages to affect yield. Experiments were thus conducted in two contrasting years (2013–2014). Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Cotton ( Gossypium hirsutum L.) is cultivated as an annual crop, its perennial nature exists predominantly under environmental factors (high precipitation, temperature and nutrient inputs etc.) that favour the vegetative growth 8 . This often consequences in greater amounts of photosynthates and nutrients to be partitioned to vegetative parts while the decreased partitioning and remobilization of reserves to developing fruits become the source of variation in seed development and size 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cotton ( Gossypium hirsutum L.) is cultivated as an annual crop, its perennial nature exists predominantly under environmental factors (high precipitation, temperature and nutrient inputs etc.) that favour the vegetative growth 8 . This often consequences in greater amounts of photosynthates and nutrients to be partitioned to vegetative parts while the decreased partitioning and remobilization of reserves to developing fruits become the source of variation in seed development and size 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous application of plant growth regulators (PGRs) is a well-known strategy to improve the crop physiological performance, nutrient dynamics within plant body and crop yield under normal and stressed conditions in agro-ecosystem 8 , 31 33 . Some studies have provided the ground basis that exogenously applied PGRs improve the nutrient uptake and accumulation within the plant body 34 , 35 .…”
Section: Introductionmentioning
confidence: 99%
“…In two years of evaluation, the PGR management did not affect lint yield (Tables 5 and 6). Studies with two or more years of field experiment or different locations have shown that mepiquat chloride responses in yield are dependent upon environmental conditions (Zhao et al 2017), such as season length, because the mepiquat chloride treatment increases fruit retention at lower fruiting branches. In years with a short growing season, mepiquat chloride tends to increase yield (Kerby et al 1986).…”
Section: Resultsmentioning
confidence: 99%
“…set at lower nodes and fewer at the top, if compared with non-treated plants, and Zhao et al (2017) reported an increase in lint yield, as a result of PGR application in early cotton growth stages. However, this response was dependent of environmental conditions and cultivar.…”
Section: Abstract Resumomentioning
confidence: 90%
“…It is also observed that Pix at 1500 ml/500 litres of water at bud formation is more effective for obtaining more number of bolls/plant and maximum seed cotton yield/plots as well as seed cotton yield kg ha -1 (Vistro et al, 2017). Zhao et al, (2017) opined that cotton yield responses to the MC, are associated with climate, cultivar, and plant population and showed that MC application at the seedling, early bloom, and full bloom stages significantly increased the cotton yields by 5.6, 5.0, and 6.1%, respectively. Late MC application of 45.0-90.0 g ha −1 at the posttopping stage is necessary for vigorous cotton cultivars to facilitate the balance of vegetative and reproductive growth.…”
Section: Effect Of Mepiquat Chloride (Mc) On Growth Yield and Qualitmentioning
confidence: 99%